TOURISM MANAGEMENT AND CREATIVE ECONOMY TRAINING IN WEST BANDUNG REGENCY - Subagyo, Agus; Rohayatin, Titin; Kurnia, Dadan; Fujilestari, Noer Apptika; Munawaroh, Siti (LPPM ITB AAS Indonesia Surakarta, 2025)
The natural conditions of West Bandung Regency have quite interesting potential in the West Java region, it is proven that there are many tourist attractions that attract the attention of visitors every day, both domestic and foreign tourists. However, this tourism potential still requires more optimal management and promotion, especially for several villages or sub-districts whose tourist attractions have not yet been developed by the government or private sector. This condition is supported by local-based economic potential which can certainly support the attractiveness of the growth of village tourism. However, tourism management and promotion have not been handled professionally. This service activity aims (1) To provide understanding to MSMEs and the tourism sector in West Bandung Regency regarding tourism management and the creative economy in West Bandung Regency. (2) To increase knowledge and understanding for tourism business service entrepreneurs in West Bandung Regency by improving tourism management and the creative economy in West Bandung Regency. The implementation methods used are participatory approach, group approach, individual approach, lecture method, discussion/FGD method. Indicators of activity success can be seen from the level of community participation and the results of pre-tests and post-tests after the activity. The results of the activity show an increase in Tourism managerial capacity in preparing short-term activity plans, including promotional plans in collaboration with schools for tourism education. Creative economy activists have understood collaborative marketing strategies and online sales.